The Practice Of Siri Marriage By Police Members Judging From The Regulation Of The Chief Of The Police Of The Republic Of Indonesia Number 6 Of 2018 - Zetria Erma; Taufika Hidayati (LEGAL BRIEF, 2022)
Currently, many unregistered marriages are carried out, including by members of the police. The purpose of this study was to identify and analyze unregistered marriages carried out by members of the police with the aim of having more than 1 (one) wife or having polygamy and the sanctions in terms of the Chief of Police Regulation No. 6 of 2018. This type of research is normative with a legal approach. The type of data used is secondary data consisting of primary, secondary and tertiary legal materials, while data analysis is carried out qualitatively. Members of the police are not allowed to carry out unregistered marriages to have more than 1 (one) polygamous wife because they violate Article 4 of the Regulation of the Chief of Police Number 6 of 2018 and the sanction is that they can be dishonorably dismissed (PDTH) or expelled from the Indonesian National Police Agency without receiving a salary or severance pay.